Diagnóstico inicial de endometriosis en mujeres de edad fértil que padecen dolor pélvico crónico en atención primaria de salud. - Guaman Medina, Karen Elizabeth (Machala : Universidad Técnica de Machala, 2021)
Introduction: Endometriosis, first described in 1860, is a chronic inflammatory disease, common in women of childbearing age, characterized by the implantation and growth of endometrial tissue outside the uterine cavity; affecting 30% to 80% of women with chronic pelvic pain. Objective: To describe the initial diagnosis of endometriosis in women of childbearing age suffering from chronic pelvic pain in primary health care. Materials and methods: An exhaustive search of high impact scientific books and articles, published through the PubMed, Google Academic and Cochrane databases in the last five years was conducted. Results: 22 scientifically significant bibliographies were obtained. The review revealed that a good clinical history and a careful pelvic examination are vital for diagnostic suspicion and timely therapeutic intervention; however, the aid of imaging methods and laparoscopy in conjunction with a histopathological examination will confirm the disease. Conclusion: The initial diagnosis of endometriosis, lies mainly in being a clinical diagnosis of exclusion, there is greater suspicion in women with chronic pelvic pain, dysmenorrhea, dyspareunia and infertility. In primary health care, sufficient importance should be given to the chronic pelvic pain referred by the users and to deepen its investigation, because it delays the initial diagnosis of endometriosis and therefore the timely therapeutic intervention.
Introducción: La endometriosis descrita por primera vez en 1860, es una enfermedad inflamatoria crónica, común en mujeres de edad fértil, caracterizada por la implantación y el crecimiento de tejido endometrial fuera de la cavidad uterina; afectando del 30% al 80% en mujeres con dolor pélvico crónico. Objetivo: Describir el diagnóstico inicial de endometriosis en mujeres de edad fértil que padecen dolor pélvico crónico en atención primaria de salud. Materiales y métodos: Se realizó una búsqueda exhaustiva de libros y artículos científicos de alto impacto, publicados a través de la base de datos de PubMed, Google Académico y Cochrane en los últimos cinco años. Resultados: Se obtuvieron 22 bibliografías de trascendencia científica, la revisión reveló que la realización de una buena historia clínica y un examen pélvico cuidadoso son vitales para la sospecha diagnóstica e intervención terapéutica oportuna, sin embargo, la ayuda de métodos imagenológicos y la laparoscopia en conjunto con un examen histopatológico confirmarán la enfermedad. Conclusión: El diagnóstico inicial de la endometriosis, radica principalmente en ser un diagnóstico clínico de exclusión, existe una mayor sospecha en mujeres con dolor pélvico crónico, dismenorrea, dispareunia e infertilidad. En la atención primaria de salud, se debe dar suficiente importancia al dolor pélvico crónico que refieren las usuarias y profundizar su investigación, debido a que retarda el diagnóstico inicial de endometriosis y por ende la intervención terapéutica oportuna.
Keywords: ENDOMETRIOSIS; DOLOR PELVICO; DIAGNOSTICO; MANEJO MEDICO